ChemInform Abstract: Efficient Protocol for the Synthesis of Novel Spiro[acenaphthylene‐1, 2′‐pyrrolidin]‐2‐one Compounds. Issue 5 (January 2016) - Lin, Yan; Fu, Zhijie; Shen, Tianhua; Che, Fengfeng; Song, Qingbao
Abstract: 21 Title compounds are prepared by a catalyst‐free 1, 3‐dipolar cycloaddition of azomethine ylides formed in situ from (I) and (III) with chalcones (II).